Effect of acupuncture on somatic symptom disorder: a systematic review and meta-analysis - Zhao, Feixue; Wang, Weiming; Feng, Xinyao; Li, Jinyu; Gang, Weijuan; Jing, Xianghong; Chen, Huan; Liang, Ying (Frontiers in Medicine, 2025)
ObjectiveThe rising prevalence of somatic symptom disorder (SSD) lacks specific treatment options. While acupuncture shows promise for mental health, its efficacy for SSD remains unclear. This systematic review and meta-analysis aims to clarify the evidence on acupuncture’s effectiveness for SSD.MethodsEight databases including PubMed, Embase, Cochrane Library, Web of Science (WoS), China National Knowledge Internet (CNKI), etc. were searched from the inception to 15 March 2024. Randomized controlled trials (RCTs) that assessed the effect of acupuncture used alone or in combination with other therapies for SSD were included. Two independent reviewers performed study screening and data extraction. Risk of bias of included studies was assessed using Cochrane Risk-of-Bias (RoB) tool version 2. Meta-analysis was conducted where applicable.ResultsOut of 9,526 articles, 5 studies with 376 patients were selected. Four of the studies showed the pooled estimates of mean difference in the change of HAMA scores between acupuncture plus paroxetine or duloxetine group and medication alone group were statistically significant at week 4 (−1.94, 95%CI: −3.71 to −0.17; p = 0.03) with borderline significance at week 6/8 (−3.17, 95%CI: −6.38 to 0.04; p = 0.05) from baseline. The pooled mean difference in change of numeric rating scale (NRS) score was not statistically significant between acupuncture plus duloxetine group and duloxetine alone group at week 2 (−1.25, 95%CI: −3.03 to 0.53; p = 0.17), 4 (−0.96; 95%CI: −2.30 to 0.38; p = 0.16), and 6/8 (−1.27, 95%CI: −3.81 to 1.26; p = 0.33) from baseline. Adverse event rates were comparable between acupuncture plus SSRI/SNRI and SSRI/SNRI alone, except in the comparison of floating acupuncture with placebo versus simulated floating acupuncture with duloxetine. All studies exhibited bias concerns or high risk of bias. Certainty of all outcomes was judged to be low or very low by using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach.ConclusionOur findings indicated potential added benefits of acupuncture combined with SSRI/SNRI for SSD-related anxiety, although effects on pain were inconsistent. High-quality RCTs with larger sample sizes are required to confirm acupuncture’s efficacy and safety for SSD.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024537063, Identifier CRD42024537063.